2010
DOI: 10.1111/j.1467-7652.2009.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of antibodies in plants: status after twenty years

Abstract: SummaryThanks to their potential to bind virtually all types of molecules; monoclonal antibodies are in increasing demand as therapeutics and diagnostics. To overcome the overloading of current production facilities, alternative expression systems have been developed, of which plants appear the most promising. In this review, we focus on the expression of monoclonal IgG or IgM in plant species. We analyse the data for 32 different antibodies expressed in various ways, differing in DNA construction, transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(142 citation statements)
references
References 109 publications
6
135
1
Order By: Relevance
“…Although it was shown previously that plant cells are able to produce complex mammalian proteins like IgGs and IgAs (reviewed by ref. 30), the correct assembly of a human molecule that consists of 21 or 24 subunits (pentamers or hexamers) with more than 50 glycans and over 100 disulfide bonds is remarkable. In mammalian plasma cells IgMs are produced and assembled in a multistep process that stretches along the secretory pathway and requires the action of various chaperons (such as Erp44, ERGIC57) and even specialized organelles (ERGIC) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was shown previously that plant cells are able to produce complex mammalian proteins like IgGs and IgAs (reviewed by ref. 30), the correct assembly of a human molecule that consists of 21 or 24 subunits (pentamers or hexamers) with more than 50 glycans and over 100 disulfide bonds is remarkable. In mammalian plasma cells IgMs are produced and assembled in a multistep process that stretches along the secretory pathway and requires the action of various chaperons (such as Erp44, ERGIC57) and even specialized organelles (ERGIC) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional IgG production in plants relies on expression of H and L chains from two independent transcription units (23,39). To develop a simple yet robust production platform, we took advantage of the subtilisin-like processing protease kex2p (40,41) and a tobamoviral replicon vector (28), whereby H and L chains are simultaneously and rapidly overexpressed from a single polypeptide transgene.…”
Section: Resultsmentioning
confidence: 99%
“…IgG molecules produced in plants, like those of human origin, are commonly glycosylated at Asn297 in the Fc region; however, the compositions of plant N-glycans slightly differ from mammalian counterparts, as represented by ␤(1,2)-linked xylose and ␣(1,3)-linked fucose (24,39,49). In fact, immunoblot analysis using plant-specific glycan-recognizing Abs (50) showed that VRC01p, but not VRC01 HEK , bear such carbohydrate structures (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these antibodies boost the immune system once in the body, but other ones do not subcellular localization, which do not allow the antibody to be correctly secreted. 37 The first mAb designed by a biomolecular engineering approach and approved by the FDA in 1997 was rituximab in the right form (correct folding and posttranslational modification) and with the desired biological function. 36 However, studies on plant-based antibodies have indicated that there are still drawbacks regarding expression, proteolytic degradation and Hodgkin lymphoma and demonstrated that 74% of the patients had an either complete or partial response, and on average, the response to the therapy persisted for six to seven months.…”
Section: Antibodiesmentioning
confidence: 99%